Garra orontesi, a new species from the Orontes River drainage (Teleostei: Cyprinidae) - Bayçelebi̇, Esra; Kaya, Cüneyt; Turan, Davut; Freyhof, Jörg (Zootaxa, 2021)
Garra orontesi, new species, is described from the Orontes River drainage in the eastern Mediterranean Sea basin in Turkey and Syria. It is distinguished from its congeners in the Mediterranean Sea basin and adjacent Mesopotamia by possessing 17–21 gill rakers on the lower part of the first gill arch, the pelvic-fin origin usually below the second branched dorsal-fin ray, 8½ branched dorsal-fin rays, usually 2–3 scales between the tip of the pectoral and pelvic-fin origins, and no tubercles behind the upper posterior eye margin. It is also distinguished by a minimum K2P distance of 2.7% in its COI barcode region against G. rufa, and 3.9% against the geographically adjacent G. turcica.